Exploring Religious Moderation through the Lens of Pancasila's First Precept: Insights from the 2024 Collaborative KKN Program - Zahrotun Nikmah; M. Nasyat Fayyadh U; Naufan Sadida Rashif; Muhammad Zaenaal M (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2024)
The connection between religious moderation and the first principle of Pancasila is that every religious follower believes in the One Supreme God they worship, but many Indonesians have limited understanding of religions other than their own. This lack of knowledge in society has inspired the author to address the issue and offer insights through this article. The research employs a qualitative method with a case study approach. Each religion interprets the concept of One God differently, but in Indonesia, they share common ground regarding the belief in a Supreme Being. This divine concept aligns with the First Principle of Pancasila. The first principle serves as a foundation for religious moderation, representing various religions in Indonesia without favoring any single faith. This reflects the core of Indonesia's ideology.